2000
DOI: 10.1016/s0022-5223(00)70215-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HLA antibody binding to HLA class I molecules induces proliferation of airway epithelial cells: A potential mechanism for bronchiolitis obliterans syndrome

Abstract: These data indicate that anti-HLA antibodies have the ability to stimulate airway epithelial cell proliferation and that they may play an important role in the development of bronchiolitis obliterans syndrome. Prevention of HLA sensitization and immunosuppression with agents capable of blocking indirect antigen presentation and the humoral immune response against the allograft may be pivotal in preventing the development of bronchiolitis obliterans syndrome after lung transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…A number of studies have suggested possible mechanistic effects of HLA-specific antibodies in the development of obstructive airway disease. [37][38][39][40][41] The majority of these studies utilized W6/32, a monoclonal antibody directed against a monomorphic determinant on HLA Class I molecules. Ligation of W6/32 to epithelial cells has been shown to cause cell proliferation, production of growth factors and chemotactic factors, as well as cell death through apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested possible mechanistic effects of HLA-specific antibodies in the development of obstructive airway disease. [37][38][39][40][41] The majority of these studies utilized W6/32, a monoclonal antibody directed against a monomorphic determinant on HLA Class I molecules. Ligation of W6/32 to epithelial cells has been shown to cause cell proliferation, production of growth factors and chemotactic factors, as well as cell death through apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In lung allografts, immune responses targeted against the epithelial cells have been thought to play a crucial role in chronic rejection of the transplanted lungs (3)(4)(5)(6). Using primary airway epithelial cell as targets, we analyzed the presence of antiepithelial Abs in a subset of lung transplant recipients with no detectable anti-HLA Abs by both complement-dependent assays as well as solid-phase assays (ELISA and flow cytometry) for the detection of Abs against HLA.…”
Section: Discussionmentioning
confidence: 99%
“…T he development of bronchiolitis obliterans syndrome (BOS) 4 remains the Achilles heel of human lung transplantation. BOS occurs in nearly all allografts by 10 years after transplant and is the main cause of morbidity and mortality following lung transplantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During acute cellular rejection, there is an increased ratio of IgG2/IgG1 within the lung allograft, suggesting local upregulation of Th1 activity (93). Although non-complementfixing antibodies can activate bronchial epithelial cells by crosslinking antigens (94), recent studies in transplants other than the lung implicate complement activation in the pathogenesis of rejection. For example, systemic activation of complement by cobra venom in rats causes pulmonary vascular leakage that can be prevented by blocking C5a (95).…”
Section: Humoral Immunitymentioning
confidence: 99%